The effects of equinox phenomenon on climate change / Zildawarni Irwan ... [et al.] - Irwan, Zildawarni; Wan Kamarudin, Wan Farahiyah; Mat Amin, Abdul Rahman; Muhammud, Adida; Muda, Siti Munirah; Mohd. Akhir, Noor Erni Fazlina; Abdullah, Salihah (2019)
In recent years, Malaysia has been experienced with the weather changes especially in increasing of the temperature. The highest temperature usually occurs during equinox. Equinox is the phenomenon when the sun is directly above the Earth's equator and this happens twice a year. Therefore, this study is carried out to determine the effects of equinox on climate change for five consecutive years. The information of this study was obtained from Malaysian Meteorological Department. The study involved three states and one federal territory in Peninsular Malaysia, namely Alor Setar (Kedah), Kota Bharu (Kelantan), Johor Bahru (Johor) and Kuala Lumpur. These states were chosen based on their location in North, East, South and West of Peninsular Malaysia. As a result, the overall mean temperature at all stations is in the range of 27°C to 30°C. The analysis revealed that the mean temperature in March showed significant increase from year 2011 to 2015 in all stations and Alor Setar recorded the highest mean temperature. However, other factors are also needed to be considered to the rising of the temperature such as El Nino phenomenon, amount of rainfall, number of rain days, Southwest and Northeast Monsoon seasons and others.